HUBUNGAN MANAJEMEN DIRI DENGAN PRESTASI BELAJAR MAHASISWA BIMBINGAN KONSELING SEMESTER IV UNIVERSITAS RIAU - Rahmadani, Haryati; Arlizon, Raja; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Entering the world of college, students must adapt not to expect too much guidance and counseling such as high school. Students must be given the independence of learning to achieve maturity to help him become a student of knowledge and religion. One of the students independence is by self-management or can be called self-management. The role of self-management is needed in learning activities, because self-management is one of the internal factors that affect learning. Good self-management is the driving force and motivator for individuals to learn, so that in individual learning will be more excited and not quickly bored in learning materials are learned and along with this can improve learning achievement. The purpose of this study is 1) to know the picture of student self-management. 2) To know the picture of student achievement. 3) To know the relationship of self-management with student achievement. Hypothesis in the proposed there is a positive and significant relationship between self-management with student learning achievement. The subjects of the study were Student Guidance and Counseling for the fourth semester of Universitas Riau, amounting to 64 people with the technique of determining the number of samples is called the total sampling ie the total sample is the whole of the population. Data collection using questionnaire about self management and student's Indeks Prestasi Komulatif data. Data analysis technique used is product moment analysis. Based on the calculation results obtained correlation coefficient value (r) of 0.466 with significant 0.000 <0.05. This shows that there is a relationship of self-management with student achievement. Effective contribution given by self management to learning achievement of 20,4% indicated by coefficient of Adjusted R Squared = 0,204, it still there are 79,6% other factors influencing learning achievement of intelligence, interest, environment.Keywords:Self-management,learning achievement2